Improving health management through clinical decision support systems - Moon, Jane D., 1962-; Galea, Mary P., 1951-; IGI eBooks; IGI Global (Hershey, Pennsylvania (701 E. Chocolate Avenue, Hershey, PA 17033, USA) : IGI Global, 2016)
"This book brings together a series of chapters focused on the technology, funding, and future plans for improved organization and decision-making through medical informatics"--Provided by publisher.
Overview of clinical decision support systems in healthcare / Jane Dominique Moon, Mary P. Galea -- Online spatial HIV/AIDS surveillance and monitoring system for Nigeria / Peter Adebayo Idowu -- Pain assessment through facial expression / Sanjay Kumar Singh, V. Rastogi, S. K. Singh -- Developing SMS health messages for pregnant indigenous Australians using persuasive technology / Reece George -- A predictive analytic model for maternal morbidity / Edgardo Palza [and 5 others] -- St. Stephen's Hospital Hervey Bay: study of developing a digital hospital / Constance A. Harmsen, Richard N. Royle -- Developing a national registry for hemochromatosis / Indu Singh, Janelle Guerrero, Michael J. Simmonds -- Integration of automation and clinical decision support systems / Ronnel Nallas, Jane Moon -- From the margins to the mainstream: clinical costing for clinical improvement / Ronald Ma -- Clinical decision support: right approaches ensure improved clinical, cost, and efficiency gains / Steven Shaha -- Leverage healthcare data assets with predictive analytics: the example of an Australian private hospital / Nilmini Wickramasinghe, Hoda Moghimi, Jonathan L. Schaffer -- Mining electronic health records to guide and support clinical decision support systems / Jitendra Jonnagaddala [and 3 others] -- A clinical decision support system: ontology-driven approach for effective emergency management / Jalel Akaichi, Linda Mhadhbi -- Data-driven and practice-based evidence: design and development of efficient and effective clinical decision support system / Hamzah Osop, Tony Sahama -- Strategic approach towards clinical information security / Sangseo Park, Jane Moon.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed 10/03/2015).
Keywords: Medical informatics; Health services administration; Decision Support Systems, Clinical; Health Services Administration; Bioinformatics; Clinical research; Electronic health records; Future healthcare; Health information technology; Information security; Nursing informatics; Technology-based medicine; Electronic books